LOOSE FLOWER, a WUSCHEL‐like Homeobox gene, is required for lateral fusion of floral organs in Medicago truncatula. (7th January 2015) - Niu, Lifang; Lin, Hao; Zhang, Fei; Watira, Tezera W.; Li, Guifen; Tang, Yuhong; Wen, Jiangqi; Ratet, Pascal; Mysore, Kirankumar S.; Tadege, Million
Summary The Medicago truncatula WOX gene, STENOFOLIA (STF), and its orthologs in Petunia, pea, and Nicotiana sylvestris are required for leaf blade outgrowth and floral organ development as demonstrated by severe phenotypes in single mutants. But the Arabidopsis wox1 mutant displays a narrow leaf phenotype only when combined with the prs/wox3 mutant. In maize and rice, WOX3 homologs are major regulators of leaf blade development. Here we investigated the role of WOX3 in M. truncatula development by isolating the lfl/wox3 loss‐of‐function mutant and performing genetic crosses with the stf mutant. Lack of WOX3 function in M. truncatula leads to a loose‐flower (lfl) phenotype, where defects are observed in sepal and petal development, but leaf blades are apparently normal. The stf lfl double mutant analysis revealed that STF and LFL act mainly independently with minor redundant functions in flower development, but LFL has no obvious role in leaf blade outgrowth in M. truncatula on its own or in combination with STF. Interestingly, LFL acts as a transcriptional repressor by recruiting TOPLESS in the same manner as STF does, and can substitute for STF function in leaf blade and flower development if expressed under the STF promoter. STF also complements the lfl mutant phenotype in the flower if expressed under the LFL promoter. Our data suggest that the STF/WOX1 and LFL/WOX3 genes of M. truncatula employ a similar mechanism of action in organizing cell proliferation for lateral outgrowth but may have evolved different cis elements to acquire distinct functions.